Impact Of Sentinel Lymph Node Mapping In Surgical Management Of Patients With Apparent Early Stage Endometrial Carcinoma (The Review of Diabetic Studies, 2025)
Objective: To evaluate the detection rate, accuracy (sensitivity and negative predictive value), and short-term clinical impact of sentinel lymph node (SLN) mapping in patients with apparent early-stage endometrial carcinoma undergoing surgical management. Patients and Methods: A total of 150 consecutive patients with clinically apparent early-stage (FIGO stage I/II) endometrial adenocarcinoma underwent total hysterectomy with bilateral salpingo-oophorectomy and SLN mapping using a dual-tracer technique: intracervical indocyanine green (ICG) for real-time fluorescence and technetium-99m (Tc-99m) nanocolloid for gamma probe detection. All identified SLNs were excised. Complete pelvic and para-aortic lymphadenectomy was performed only for positive SLNs, high-risk histological features, or bilateral SLN non-detection. Results: The overall SLN detection rate was 95.3% (143/150), with bilateral detection in 88.7% (133/150). Among 30 patients with confirmed lymph node metastases, SLNs correctly identified metastasis in 29 cases, yielding a sensitivity of 96.7% and a false-negative rate of 3.3%. The negative predictive value was 98.6%. Patients who underwent SLN mapping alone had significantly lower postoperative complications (12% vs. 35%, p